Rainfall thresholds of shallow landslides in Wuyuan County of Jiangxi Province, China - Li Xiaochao (Open Geosciences, 2020)
Rainfall is a critical factor inducing landslides, and thus the study of rainfall thresholds is of great significance for the prediction and prevention of landslides. In June 2017, infrastructures such as electric power pylons and roads were threatened by group-occurring landslides due to continuous heavy rainfall in Wuyuan County, Jiangxi Province of China. Based on the analysis of the rainfall data from March to September in this region, the lower (92.4 mm/d) and the upper (217.1 mm/d) empirical rainfall thresholds were determined. The soil water characteristic parameters of a typical landslide were determined by laboratory tests and back-analysis. Then, the factor of safety (FOS) versus time and the mechanical response of failure process with rainfall infiltration were examined. The results showed that during rainfall infiltration, the pore-water pressure increased, while the matrix suction and the stability decreased gradually. After the rain, the FOS increased slowly to a constant value, which was smaller than the initial. The physical rainfall threshold (200 mm/d), determined using 18 numerical simulation tests considering different rainfall intensities and amounts, was consistent with the empirical rainfall threshold. The methods developed in this work provide a useful tool for the prediction of landslides under extreme rainfall conditions.